ChemInform Abstract: Ga(OTf)3 Catalyzed Synthesis of 3, 4‐Dihydropyrimidin‐2(1H)‐ones. Issue 23 (June 2015) - Xia, Jingjing; Zhang, Kehua
Abstract 2‐oxopyrimidinones, 2‐thiopyrimidinones and cyclopentapyrimidinones are prepared by Biginelli reaction in high yields in short reaction times.